2017
DOI: 10.1177/0033294117692807
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Personality Disorders in a General Population Among Men and Women

Abstract: The aim of the present study is to establish the prevalence of personality disorders (PDs) in a healthy (nonclinical) Polish population, to examine sex difference in PDs, and to show the structure of clusters which PDs form with regard to men and women. A large sample of 1460 individuals of age between 18 and 65 years was examined. The Structured Clinical Interview for Axis II was used to obtain information on PDs, the Mini International Neuropsychiatric Interview to obtain information on other disorders, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 49 publications
2
17
1
1
Order By: Relevance
“…This is in line with another study which showed that the average score for covert narcissism was higher in the Polish sample in comparison to the Dutch sample (Zondag, Van Halen, & Wojtkowiak, 2009). Furthermore, these results showed greater comorbidity of PD traits than that which has been reported in the literature (Gawda & Czubak, 2017).…”
Section: Europesupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with another study which showed that the average score for covert narcissism was higher in the Polish sample in comparison to the Dutch sample (Zondag, Van Halen, & Wojtkowiak, 2009). Furthermore, these results showed greater comorbidity of PD traits than that which has been reported in the literature (Gawda & Czubak, 2017).…”
Section: Europesupporting
confidence: 92%
“…The most frequent PDs were schizotypal (8.60%), paranoid (6.10%) and histrionic (6.10%) (Trzebińska & Gabińska, 2014). Then, a study on the prevalence of PD traits using the DSM-IV technique (the Structured Clinical Interview for the DSM-IV Axis II Disorders -SCID-II by First et al, 2010) was conducted by Gawda and Czubak (2017). A large community sample between 18 and 65 years old was randomly selected and interviewed.…”
Section: Europementioning
confidence: 99%
“…Clinically significant PDs manifest as disturbances in cognition, affects, impulse control and interpersonal relationships . The prevalence of PDs has been established as varying from 6% to 10% in population samples to 24–60% in psychiatric patient samples . PDs are found to have psychiatric comorbidity as well as an increased risk for suicide .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by Gawda and Czuback (2017) estimated the prevalence of personality disorders within the Polish population. Their sample of 1460 participants, aged between 18 and 65 years, completed the Mini International Neuropsychiatric Interview, and subsequently further demographic data was collected.…”
Section: Characterisation Of Personality Disordersmentioning
confidence: 99%